Diversity and Humanity in Islam: A Perspective of Religious Moderation - Asmanidar, Asmanidar (Prodi Studi Agama-Agama, 2023)
The important principles in Islam that emphasize simplicity, balance, tolerance, justice, and respect for differences reflect the profound teachings of Islam and play a key role in maintaining social harmony in diverse societies. Overall, religious moderation in Islam is an approach centered on values that promote tolerance, peace, and appreciation of differences. This is a relevant and essential principle in an increasingly interconnected and diverse world, where a deep understanding of Islamic teachings can help resolve conflicts and promote harmony among different religious communities. The research method used in this study is a literature review (library research), with a research approach based on the analysis and synthesis of literature relevant to the specific research topic. The literature review method can be employed to gather and analyze relevant text sources, including books, academic papers, journals, and other sources discussing diversity, humanity, and moderation in the context of Islam. The results of this research show that religious moderation provides a comprehensive overview of the importance of religious moderation in Islam and how values such as tolerance, national commitment, anti-violence, respect for tradition, welfare, justice, balance, humanity, and diversity are applied in the Islamic context. In the modern era, where communities are increasingly interconnected and global challenges such as extremism and radicalization arise, understanding and practicing religious moderation is crucial to promoting peace, harmony, and cooperation among humanity.